Gliocladium and Trichoderma in agricultural soil - LIANG Chen; LI Bao-du; LU Guo-zhong (浙江大学学报. 农业与生命科学版)
Gliocladium and Trichoderma are common fungi in agricultural soil. Several species of them were isolated and identified, great diversity was displayed in different agricultural soils of different crops, agricultural climate zones, different seasons, depths, different treated soybean cyst nematode soil, healthy and diseased crop soil. Among five crops soil samples, wheat and corn soil were found to possess the largest number of Gliocladium and Trichoderma separately. Gliocladium and Trichoderma of three major crops showed consistent changing patterns with seasonal variation. Corn soil displayed distinct vertical distribution of Trichoderma. There is a different distribution of the two fungi in diseased and healthy plant soil. Among the various isolated methods, diluted plate method is the best for isolating Gliocladium, and Trichoderma could be found in plant residue method and be tolerant to steam for two minutes. In the soybean cyst nematode soil mycobiota, the frequency of Gliocladium is higher than that of the others fungi, and Trichoderma may have the role of bioremediation in herbicide treated soil. Similarly, Gliocladium occurred frequently in different climate zones.